A stabilization synthesis strategy for atomically dispersed metal-N4 electrocatalysts via aerogel confinement and ammonia pyrolyzing. (15th December 2022) - Luo, Yi; Wu, Jiao; Chen, Yongting; Feng, Junzong; Wang, Lukai; Li, Liangjun; Jiang, Yonggang; Lei, Yongpeng; Feng, Jian
Abstract: Catalytically active metals that are atomically dispersed on supports exhibit the highest atom utilization and most cost-effective pathways for electrocatalyst design. However, the high-throughput scalable production of inexpensive, efficient, and durable atomically dispersed electrocatalysts remains challenging. Herein, a hierarchical porous carbon aerogel loaded with atomically dispersed metal-N4 (metal-N-C) was synthesized via the NH3 pyrolysis of a metal-doped polymer aerogel. This novel synthetic strategy requires the tailoring of various materials, such as metal sol, resorcinol formaldehyde sol, hydrogel, and metal-N-C. The synthetic applicability of this strategy was demonstrated via the facile synthesis of Co-N-C, Ni-N-C, and Fe-N-C. Notably, Fe-N-C exhibited a half-wave potential of approximately 0.933 V vs. reversible hydrogen electrode and lost approximately 4 mV after 5000 cycles of accelerated aging test in a 0.1 mol/L KOH solution for the oxygen reduction reaction. In a solid-state zinc-air battery, Fe-N-C exhibited a maximum power density of 167 m W cm −2, an energy density of 956 W h Kg −1, and long-term stability over 120 h, which significantly exceeds that of commercial Pt/C. The high activity and durability of Fe-N-C is attributed to the double Fe-N4 active center, where the synergistic effect of the neighboring Fe-N4 promotes oxygen dissociation and produces less H2 O2 . The developed strategy provides an aerogel-based solution for fabricating inexpensive, efficient, and durable atomically dispersed electrocatalysts with potential for high-throughput scalable production and expands the understanding of the synthesis of atomically dispersed electrocatalysts. Graphical Abstract: ga1 Highlights: Metal-N-C are synthesized via aerogel confinement and ammonia pyrolyzing. In solid-state zinc-air battery, the Fe-N-C shows 167 mW/cm 2 maximum power density, 956 Wh/Kg energy density and over 120 h cycle stability. The high activity and durability of the Fe-N-C ascribes to double Fe-N4 active-centers.